THREE CASES OF CHRONIC TRAUMATIC ANEURYSM OF THE THORACIC AORTA - KOBAYASHI, Gensou; BABA, Takako; KANAOKA, Yuji; MURAKAMI, Takashi; OSHIMA, Yu; TAMURA, Ryuji; NAKAGAWA, Yoshikiyo; YUNOKI, Yasuhiro; URUSHIHARA, Naoto; KUINOSE, Masahiko; KAWASHIMA, Ken; TANAKAYA, Koji; et al. (Japanese Journal of National Medical Services, 1997)
Three cases of chronic traumatic thoracic aneurysms were reported. Time intervals between thoracic trauma and operation varied from 5 months to 23 years. All aneurysms were located in the descending thoracic aorta. Surgical corrections were accomplished with no mortality and morbidity. Evidence of chronic traumatic thoracic aorta injury may not be revealed clinically for many years. This diagnosis should be considered in dealing with patients who have a history of severe thoracic trauma, no matter how remote.